Incorporation of industrial wastes in wood pellets - Ferreira, Eduardo Campos (2009)
ABSTRACT: The present work evaluates the incorporation of industrial wastes (Refuse Derived Fuel-RDF) into biomass for pellet production. Its influence on parameters such as pellet production, combustion and gas emissions was studied for up to 10% of residues incorporation. This approach also deals with the diverting of industrial waste from landfills. The main objectives were: increasing the heat value of the final product, diverting industrial residues with energy potential from landfill and assess the quality of different types of pellets with incorporation of industrial residues. Its implementation was carried out in three phases: selection and characterization of the different industrial residues, production of pellets from different mixtures of wastes and combustion tests. For this purpose a comprehensive characterization of the pellets, the gaseous emissions during combustion and the chemical characterization of the resulting ashes was carried out. The study has shown that the application of industrial residues is a promising route for their incorporation in pellets which should be balanced by the reduction of wastes for landfill. However a few problems were identified: higher difficulty in pelletizing and likely excessive wear of the pellet mill for some of the residues; combustion equipment requiring air supply adjustment and higher ash contents.